Preparation method of nanoscale cobaltosic oxide

Through the mixing and controlling sintering process of cobalt salt solution and composite surfactant, the problems of medium and high cost and uneven particle size of nano-scale cobalt tetraoxide preparation are solved, and simple, fast and low-cost nano-scale cobalt tetraoxide preparation are achieved, satisfying nanomaterials application requirements.

CN119191373APending Publication Date: 2024-12-27GEM JIANGSU COBALT IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411262980.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing nano-scale cobalt tetraoxide preparation process has high cost and uneven particle size in industrial production, especially the use of expensive nitrogen and vacuum drying equipment, and the particle size is large, making it difficult to meet the application needs of nanomaterials.

Method used

Use cobalt salt solution and composite surfactant to form a cobalt hydroxide slurry by controlling the stirring and temperature, and then wash, filter, blow dry and sinter. Combined with medium and low temperatures and high temperatures, a uniform small particle cobalt tetroxide is formed to avoid The process flow is simplified by using an inert atmosphere and antioxidants.

Benefits of technology

It realizes the preparation of nano-scale cobalt tetraoxide with simple, fast and low-cost steps, with uniform particle size distribution, reducing production costs, and improving the purity and particle size control effect of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191373A_ABST
    Figure CN119191373A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of nanoscale cobaltosic oxide, and belongs to the technical field of cobalt oxides. The method comprises the following steps: (1) mixing a cobalt source and a composite surfactant to form a solution A; the cobalt source is an aqueous solution of cobalt salt; the composite surfactant is formed by mixing dodecyl trimethyl ammonium chloride and polyvinyl alcohol according to the mass ratio of 1: 1; (2) preparing sodium hydroxide into a dilute alkali aqueous solution to obtain a solution B; (3) adding the solution B into a reaction kettle, and then adding the solution A at a constant speed through a feed port of the reaction kettle for feeding; the stirring speed in the reaction kettle is controlled to be 300-600 rpm, feeding is ended when the final pH value of the mixed solution is 10.5-11.5, and the feeding process is controlled to be completed within 5-10 min; cobalt hydroxide slurry is obtained; (4) carrying out washing, filter pressing and blow-drying on the obtained cobalt hydroxide slurry, and then sintering; after sintering is completed, crushing is performed, and the nanoscale cobaltosic oxide can be obtained. The method has the advantages of simple and rapid steps, low cost and uniform particle size distribution of the product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cobalt oxides, and in particular to a method for preparing nano-scale cobalt tetroxide. Background Art

[0002] Nanoscale cobalt oxide (Co3O4) is an important functional material with unique physical and chemical properties and a wide range of applications. Its nanoscale characteristics make nano cobalt oxide show a larger specific surface area and higher activity. It has good electrochemical catalytic activity and shows good stability and high efficiency in electrochemical catalytic reactions. In addition, nano cobalt oxide has magnetic properties and is suitable for fields such as magnetic materials and magnetic storage devices.

[0003] In practical applications, nano-cobalt tetroxide can be used as a cathode material for lithium-ion batteries, with high specific capacity and good cycle performance, and is suitable for electric vehicles and rechargeable devices. It is also commonly used as an electrochemical catalyst for energy conversion technologies such as water decomposition and fuel cells. In addition, nano-cobalt tetroxide is sensitive to a variety of gases and is widely used in gas sensors and gas analysis, such as carbon dioxide sensors and toxic gas detectors. In the field of photocatalysis, nano-cobalt tetroxide also has potential and can use sunlight or artificial light to catalyze the photolysis of water to produce hydrogen, so it has important application value in the field of solar water decomposition and sustainable energy.

[0004] The preparation of nano-scale cobalt oxide is an important part of the above industrial applications. For example, the Chinese invention patent with the publication number CN117999246A discloses a method for preparing modified nano-cobalt oxide, which includes the following steps: preparing a cobalt salt solution, an alkaline solution, and a sintering aid; introducing an inert gas into a reactor to replace the air therein so that the reaction is carried out in an inert atmosphere, adding the cobalt salt solution and the alkaline solution for mixed reaction, and obtaining a nano-cobalt hydroxide slurry with a moisture content of 85 wt.%-90 wt.%; filtering the nano-cobalt hydroxide slurry to obtain a squeezed nano-cobalt hydroxide slurry with a moisture content of 60 wt.%-70 wt.%; drying the squeezed nano-cobalt hydroxide slurry to obtain a dry nano-cobalt hydroxide slurry with a moisture content of less than 10 wt.%; oxidizing and crushing the dry nano-cobalt hydroxide slurry, and mixing and modifying it with the sintering aid to obtain a modified nano-cobalt oxide with a moisture content of less than 1 wt.%, and a D50 of less than 1 μm. The invention reduces the water content of nano cobalt hydroxide slurry by two steps of gradient filtration and drying; and reduces the sintering temperature by using a sintering aid as a catalyst.

[0005] The above scheme still has several technical problems in actual industrial production. The first is the extremely important cost issue in industrial production. The process requires nitrogen to be introduced during the synthesis process, and the slurry is treated by vacuum drying. Under industrial-scale production conditions, the cost of maintaining a nitrogen atmosphere is high. Nitrogen production equipment, such as cryogenic air separation units or pressure swing adsorption (PSA) nitrogen generators, requires a large initial investment. In addition, the maintenance and operation of nitrogen production equipment will also incur continuous costs. In the nitrogen production process, especially cryogenic air separation technology, a large amount of energy is required to cool the air to a liquefied state and separate nitrogen by distillation. The energy consumption of this process is an important part of the nitrogen production cost. The vacuum drying process is a drying technology carried out under low pressure. It can achieve rapid evaporation of water in the material at a lower temperature and is suitable for drying heat-sensitive materials. The efficiency of vacuum drying is usually not as high as that of conventional drying methods, because under vacuum conditions, although the evaporation rate of water is accelerated, the heat and mass transfer efficiency of the entire system is limited. Vacuum drying equipment usually needs to be equipped with a vacuum pump and other related vacuum systems, which will increase the initial investment and operating costs of the equipment. In addition to the cost, the D50 index of the nano-scale cobalt tetroxide prepared by the above scheme is below 1 μm, which is still a relatively large particle size for the use of nanomaterials.

[0006] In summary, providing a method for preparing nano-scale cobalt tetroxide with simple steps, rapidity, low cost and uniform product particle size distribution is of great significance for expanding the application of nano-scale cobalt tetroxide in various fields. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, in a first aspect of the present invention, a method for preparing nano-scale cobalt trioxide with simple steps, rapidity, low cost and uniform product particle size distribution is provided, comprising the following steps: (1) mixing a cobalt source and a composite surfactant to form a solution A; wherein the cobalt source is an aqueous solution of a cobalt salt; and the composite surfactant is a mixture of dodecyltrimethylammonium chloride and polyvinyl alcohol in a mass ratio of 1:1; (2) preparing sodium hydroxide into a dilute alkaline aqueous solution to obtain solution B; (3) adding solution B to the reactor, and then adding solution A at a uniform speed through the feed port of the reactor for feeding; controlling the stirring rate in the reactor to be 300-600 rpm, and stopping the feeding when the endpoint pH of the mixed solution reaches 10.5-11.5, and controlling the feeding process to be completed within 5-10 min; obtaining cobalt hydroxide slurry; (4) The obtained cobalt hydroxide slurry is washed, filtered, dried and then sintered; after sintering, it is crushed to obtain nano-scale cobalt tetroxide.

[0008] Different cobalt salts have different solubility in water, which will affect the synthesis process of cobalt hydroxide. Among them, cobalt chloride, cobalt sulfate, and cobalt nitrate have good solubility in water and are suitable as raw materials for the production of cobalt hydroxide.

[0009] Preferably, in step (1), the cobalt salt includes at least one of cobalt chloride, cobalt sulfate and cobalt nitrate.

[0010] In this process, the cobalt concentration of the cobalt source is appropriately controlled within the range of 90-160 g / L. The cobalt concentration will directly affect the quality of the final product and the efficiency of the production process. If the cobalt concentration is too high, the quality of the cobalt precipitation product will be unstable, and the cobalt grade in the obtained cobalt hydroxide will be low. In addition, too high a cobalt concentration may affect the uniformity of the precipitation reaction and the growth of the particles, thereby affecting the morphology and particle size distribution of the cobalt hydroxide. If the cobalt concentration is too low, a larger volume of solution needs to be processed to obtain the same amount of cobalt hydroxide. Therefore, in order to ensure the high quality and production efficiency of cobalt hydroxide, the cobalt concentration of the cobalt source needs to be controlled within the above-mentioned appropriate range.

[0011] Preferably, in step (1), the cobalt concentration of the cobalt source is 90-160 g / L.

[0012] In the composite dispersant, the suitable molecular weight range of polyvinyl alcohol is 6000-30000. Its advantage in this process is mainly reflected in its ability to provide good dispersibility and stability. Within this molecular weight range, polyvinyl alcohol can effectively disperse cobalt hydroxide solid particles uniformly in the liquid medium, prevent particle agglomeration and precipitation, thereby improving the uniformity and stability of the product and optimizing the particle size of the product.

[0013] Preferably, in step (1), the molecular weight of the polyvinyl alcohol is 6000-30000.

[0014] Preferably, in step (1), the amount of the composite surfactant used is 5 wt.‰-1 wt.% of the cobalt source.

[0015] Controlling the concentration of the sodium hydroxide aqueous solution at 5 wt.%-10 wt.% can ensure that the reactants are fully contacted, promote the effective combination of cobalt ions and hydroxide ions, and thus increase the yield of cobalt hydroxide. Lower sodium hydroxide concentrations help reduce the occurrence of side reactions, such as uneven crystal growth caused by supersaturation, which helps to obtain higher purity cobalt hydroxide products.

[0016] Preferably, in step (2), the concentration of solution B is 5 wt.%-10 wt.%.

[0017] Preferably, in step (3), the amount of solution B added to the reactor is 25%-50% of the volume of the reactor.

[0018] Controlling the reaction temperature in the reactor at 15-55 °C helps improve reaction efficiency, control product morphology, reduce side reactions, save energy and reduce consumption, and improve the quality of the final product. Within this temperature range, the molecular motion of the reactants is accelerated, which helps to increase the reaction rate, thereby improving the overall reaction efficiency. From a thermodynamic point of view, the combination of cobalt ions and hydroxide is already spontaneous at a lower temperature. Properly increasing the temperature usually increases the reaction rate, but further increasing the temperature will not significantly increase the conversion rate of the reaction. Within this temperature range, the occurrence of side reactions can be reduced to a certain extent, and the morphology and particle size of cobalt hydroxide can be better controlled.

[0019] Preferably, in step (3), the temperature of the reactor is 15-55 °C.

[0020] Preferably, in step (4), the sintering is first performed at 300-400°C for 3-6 h, and then the temperature is increased to 500-700°C for 3-6 h.

[0021] Based on the above technical scheme, the inventive concept of the present invention is that in industrial production, antioxidants are added or nitrogen is passed to create an inert atmosphere, which is essentially to ensure that the product is pure phase cobalt hydroxide. The pure phase cobalt hydroxide color is pink. If nitrogen is not passed or antioxidants are added in the actual preparation, the chemical composition of its product is still mainly cobalt hydroxide, but the color is slightly oxidized and light coffee color. For the preparation of cobalt tetroxide, no matter whether cobalt hydroxide is slightly oxidized, it is finally completely oxidized to cobalt tetroxide by burning, so the present invention does not need an inert atmosphere or add an oxidant in the early stage, which will help to reduce the cost of production. In terms of particle size control, the present invention first uses a rapid reaction process. In the rapid reaction, the nucleation process is often very rapid, resulting in the formation of a large number of crystal nuclei in a short time. The rapid formation of these crystal nuclei consumes a large amount of reactants, thereby forming a higher concentration gradient in the solution. At the same time, due to limited reaction time, the growth process of the crystal nucleus may be relatively slow and cannot be fully carried out. This unbalanced competition between nucleation rate and growth rate causes the crystal nucleus to expand mainly in the horizontal direction, while the growth in the vertical direction is restricted, thus forming thinner nanosheets, which are easier to break into small particles through subsequent sintering. Not only that, the addition of composite surfactants can improve the agglomeration of the generated cobalt hydroxide, so that small particles will not melt together during sintering, resulting in an increase in particle size. Finally, sintering at medium and low temperatures can reduce the surface energy between particles, making them more dispersed and preventing them from fusing together during the sintering process; then sintering the dispersed nanosheets at high temperatures to break them into smaller nanoparticles can help promote the complete phase transformation of cobalt hydroxide into cobalt oxide and ensure purity.

[0022] Compared with the prior art, the present invention has the following advantages and beneficial effects: The invention provides a method for preparing nano-scale cobalt tetroxide, which has the advantages of simple and quick steps, low cost and uniform product particle size distribution. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a scanning electron microscope (SEM) image of the nano-scale cobalt tetroxide prepared in Example 1; Figure 2 This is a SEM image of nano-scale cobalt oxide prepared in Example 2; Figure 3 This is a SEM image of cobalt tetroxide prepared in Comparative Example 1; Figure 4 This is the SEM image of cobalt tetroxide prepared in Comparative Example 2. DETAILED DESCRIPTION

[0024] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0025] Example 1 The preparation method of nano-scale cobalt tetroxide comprises the following steps: (1) A cobalt source and a composite surfactant are mixed to form a solution A; wherein the cobalt source is an aqueous solution of cobalt chloride, and the cobalt concentration is 130 g / L; the composite surfactant is prepared by mixing dodecyltrimethylammonium chloride and polyvinyl alcohol in a mass ratio of 1:1, and the addition amount thereof is 5 wt.‰ of the cobalt source; (2) preparing sodium hydroxide into a dilute alkaline aqueous solution with a concentration of 8 wt.% to obtain solution B; (3) adding solution B to the reactor in an amount of 30% of the volume of the reactor, with the temperature in the reactor being 25°C, and then adding solution A at a uniform rate through the four feed ports of the reactor for feeding; controlling the stirring rate in the reactor to be 600 rpm, and stopping the feeding when the endpoint pH of the mixed solution reaches 10.5-11.5, and controlling the feeding time to be 5 min; obtaining cobalt hydroxide slurry; (4) The obtained cobalt hydroxide slurry is washed, filtered, dried, and then sintered, first at 300 °C for 3 h and then at 500 °C for 3 h. After sintering, it is crushed to obtain nano-scale cobalt tetroxide.

[0026] The D50 and D100 of nano-cobalt tetroxide were tested. The D50 of this embodiment was 0.112 μm and the D100 was 3.145 μm. The microscopic morphology of nano-cobalt tetroxide was observed by SEM. Figure 1The above results show that after sintering, the flake structure of cobalt hydroxide is broken into a finer dot structure, which meets the preparation requirements of the present invention.

[0027] Example 2 The preparation method of nano-scale cobalt tetroxide comprises the following steps: (1) A cobalt source and a composite surfactant are mixed to form a solution A; wherein the cobalt source is an aqueous solution of cobalt chloride, and the cobalt concentration is 130 g / L; the composite surfactant is prepared by mixing dodecyltrimethylammonium chloride and polyvinyl alcohol in a mass ratio of 1:1, and the addition amount thereof is 5 wt.‰ of the cobalt source; (2) preparing sodium hydroxide into a dilute alkaline aqueous solution with a concentration of 8 wt.% to obtain solution B; (3) adding solution B to the reactor in an amount of 30% of the volume of the reactor, with the temperature in the reactor being 25°C, and then adding solution A at a uniform rate through the four feed ports of the reactor for feeding; controlling the stirring rate in the reactor to be 600 rpm, and stopping the feeding when the endpoint pH of the mixed solution reaches 10.5-11.5, and controlling the feeding time to be 5 min; obtaining cobalt hydroxide slurry; (4) The obtained cobalt hydroxide slurry is washed, filtered, dried and then sintered, first at 400 °C for 3 h and then at 600 °C for 3 h. After sintering, it is crushed to obtain nano-scale cobalt tetroxide.

[0028] The D50 and D100 of nano-cobalt tetroxide were tested. The D50 of this embodiment was 0.387 μm and the D100 was 7.253 μm. The microscopic morphology of nano-cobalt tetroxide was observed by SEM. Figure 2 The above results show that the sintering temperature is too high and the broken point-like structure is melted to form larger spherical particles, resulting in a particle size higher than that of Example 1, but still better than the level of the prior art.

[0029] Example 3 The preparation method of nano-scale cobalt tetroxide comprises the following steps: (1) A cobalt source and a composite surfactant are mixed to form a solution A; wherein the cobalt source is an aqueous solution of cobalt sulfate, and the cobalt concentration is 90 g / L; the composite surfactant is prepared by mixing dodecyltrimethylammonium chloride and polyvinyl alcohol in a mass ratio of 1:1, and the addition amount thereof is 5 wt.‰ of the cobalt source; (2) preparing sodium hydroxide into a dilute alkaline aqueous solution with a concentration of 5 wt.% to obtain solution B; (3) adding solution B to the reactor in an amount of 25% of the volume of the reactor, with the temperature in the reactor being 15°C, and then adding solution A at a uniform rate through the four feed ports of the reactor for feeding; controlling the stirring rate in the reactor to be 300 rpm, and stopping the feeding when the endpoint pH of the mixed solution reaches 10.5-11.5, and controlling the feeding time to be 5 min; obtaining cobalt hydroxide slurry; (4) The obtained cobalt hydroxide slurry is washed, filtered, dried and then sintered, first at 300 °C for 6 h and then at 500 °C for 6 h. After sintering, it is crushed to obtain nano-scale cobalt tetroxide.

[0030] Example 4 The preparation method of nano-scale cobalt tetroxide comprises the following steps: (1) A cobalt source and a composite surfactant are mixed to form a solution A; wherein the cobalt source is an aqueous solution of cobalt nitrate, and the cobalt concentration is 160 g / L; the composite surfactant is prepared by mixing dodecyltrimethylammonium chloride and polyvinyl alcohol in a mass ratio of 1:1, and the addition amount thereof is 1 wt.% of the cobalt source; (2) preparing sodium hydroxide into a dilute alkaline aqueous solution with a concentration of 10 wt.% to obtain solution B; (3) adding solution B to the reactor in an amount of 50% of the volume of the reactor, the temperature in the reactor being 55°C, and then adding solution A at a uniform rate through the four feed ports of the reactor for feeding; controlling the stirring rate in the reactor to be 600 rpm, and stopping the feeding when the endpoint pH of the mixed solution reaches 10.5-11.5, and controlling the feeding time to be 10 min; obtaining cobalt hydroxide slurry; (4) The obtained cobalt hydroxide slurry is washed, filtered, dried and then sintered, first at 400 °C for 3 h and then at 700 °C for 3 h. After sintering, it is crushed to obtain nano-scale cobalt tetroxide.

[0031] Comparative Example 1 The preparation method of cobalt tetroxide comprises the following steps: (1) A cobalt source and a composite surfactant are mixed to form a solution A; wherein the cobalt source is an aqueous solution of cobalt chloride, and the cobalt concentration is 130 g / L; the composite surfactant is prepared by mixing dodecyltrimethylammonium chloride and polyvinyl alcohol in a mass ratio of 1:1, and the addition amount thereof is 5 wt.‰ of the cobalt source; (2) preparing sodium hydroxide into a dilute alkaline aqueous solution with a concentration of 8 wt.% to obtain solution B; (3) adding solution B to the reactor in an amount of 30% of the volume of the reactor, with the temperature in the reactor being 25°C, and then adding solution A at a uniform rate through the four feed ports of the reactor for feeding; controlling the stirring rate in the reactor to be 600 rpm, and stopping the feeding when the endpoint pH of the mixed solution reaches 10.5-11.5, and controlling the feeding time to be 5 min; obtaining cobalt hydroxide slurry; (4) The obtained cobalt hydroxide slurry is washed, filtered, dried, and then sintered at 750°C for 6 hours. After sintering, it is crushed to obtain cobalt tetroxide.

[0032] The D50 and D100 of cobalt tetroxide were tested. The D50 of this comparative example was 0.911 μm and the D100 was 23.247 μm. The microscopic morphology of nano-cobalt tetroxide was observed by SEM. Figure 3 The above results show that when the sintering temperature is too high, the flake structure melts to form a larger spinel structure, which causes the particle size of the product to increase.

[0033] Comparative Example 2 The preparation method of cobalt tetroxide comprises the following steps: (1) A cobalt source is used as solution A; wherein the cobalt source is an aqueous solution of cobalt chloride, and the cobalt concentration is 130 g / L; (2) preparing sodium hydroxide into a dilute alkaline aqueous solution with a concentration of 8 wt.% to obtain solution B; (3) adding solution B to the reactor in an amount of 30% of the volume of the reactor, with the temperature in the reactor being 25°C, and then adding solution A at a uniform rate through the four feed ports of the reactor for feeding; controlling the stirring rate in the reactor to be 600 rpm, and stopping the feeding when the endpoint pH of the mixed solution reaches 10.5-11.5, and controlling the feeding time to be 5 min; obtaining cobalt hydroxide slurry; (4) The obtained cobalt hydroxide slurry is washed, filtered, dried, and then sintered, first at 300 °C for 3 h and then at 500 °C for 3 h. After sintering, it is crushed to obtain cobalt tetroxide.

[0034] The D50 and D100 of cobalt tetroxide were tested. The D50 of this comparative example was 0.773 μm and the D100 was 18.351 μm. The microscopic morphology of nano-cobalt tetroxide was observed by SEM. Figure 4 The above results show that without adding surfactant, the agglomeration phenomenon is serious, the size and morphology of the cobalt oxide particles after sintering are different, and the formed sheet structure is thick, which is difficult to meet the preparation requirements.

[0035] In summary, the present invention firstly makes the generated cobalt hydroxide nanosheets thinner through a rapid reaction process, and the nanosheets are more easily broken into small particles by sintering. In addition, the addition of a composite surfactant can improve the agglomeration phenomenon of the generated cobalt hydroxide, so that the small particles will not melt together during sintering, resulting in an increase in particle size. Finally, by first sintering at a medium or low temperature, the surface energy between the particles can be reduced, thereby making them more dispersed and preventing them from fusing together during the sintering process; and then sintering the dispersed nanosheets at a high temperature to break them into smaller nanoparticles, which helps to promote the complete phase transformation of cobalt hydroxide into cobalt oxide and ensure purity.

[0036] The preferred specific embodiments of the present invention are described in detail above. It should be understood that a person skilled in the art can make many modifications and changes based on the concept of the present invention without creative work. Therefore, any technical solution that can be obtained by a person skilled in the art through logical analysis, reasoning or limited experiments based on the concept of the present invention on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. A method for preparing nano-scale cobalt tetroxide, characterized in that: The steps include: (1) mixing a cobalt source and a composite surfactant to form a solution A; wherein the cobalt source is an aqueous solution of a cobalt salt; and the composite surfactant is a mixture of dodecyltrimethylammonium chloride and polyvinyl alcohol in a mass ratio of 1:1; (2) preparing sodium hydroxide into a dilute alkaline aqueous solution to obtain solution B; (3) adding solution B to the reactor, and then adding solution A at a uniform speed through the feed port of the reactor for feeding; controlling the stirring rate in the reactor to be 300-600 rpm, and stopping the feeding when the endpoint pH of the mixed solution reaches 10.5-11.5, and controlling the feeding process to be completed within 5-10 min; obtaining cobalt hydroxide slurry; (4) The obtained cobalt hydroxide slurry is washed, filtered, dried and then sintered; after sintering, it is crushed to obtain nano-scale cobalt tetroxide.

2. The method for preparing nano-scale cobalt tetroxide according to claim 1, characterized in that: In the step (1), the cobalt salt includes at least one of cobalt chloride, cobalt sulfate and cobalt nitrate.

3. The method for preparing nano-scale cobalt trioxide according to claim 1, characterized in that: In the step (1), the cobalt concentration of the cobalt source is 90-160 g / L.

4. The method for preparing nano-scale cobalt tetroxide according to claim 1, characterized in that: In the step (1), the molecular weight of the polyvinyl alcohol is 6000-30000.

5. The method for preparing nano-scale cobalt trioxide according to claim 1, characterized in that: In the step (1), the amount of the composite surfactant used is 5 wt.‰-1 wt.% of the cobalt source.

6. The method for preparing nano-scale cobalt trioxide according to claim 1, characterized in that: In the step (2), the concentration of solution B is 5 wt.%-10 wt.%.

7. The method for preparing nano-scale cobalt tetroxide according to claim 1, characterized in that: In the step (3), the amount of solution B added to the reactor is 25%-50% of the volume of the reactor.

8. The method for preparing nano-scale cobalt trioxide according to claim 1, characterized in that: In the step (3), the temperature of the reactor is 15-55°C.

9. The method for preparing nano-scale cobalt trioxide according to claim 1, characterized in that: In the step (4), the sintering is first carried out at 300-400°C for 3-6 hours, and then raised to 500-700°C for 3-6 hours.